State-owned enterprises privatizations in Costa Rica: How much could it reduce fiscal deficit? - Espinoza Rodríguez, Julio (2021)
The literature review on privatizations leads to mixed and contradictory conclusions on the effect of privatizations on the economy. Therefore, the conclusions of each study must be discerned and adapted to each reality, so that its implementation in practice does not have negative effects on society. Precisely in the case of Costa Rica, some have presented the idea that the sale of state-owned assets solves a large part -and some the solution- of the country’s debt, which is not true, because the impact of sales is infinitesimal and it seems that those who propose it as the "cure-all remedy", either did not make the particular calculations or are carried away by ideological approaches or simply, by a mimic effect.